The Melancholies of Failing States in the Global South: A Glimpse at West Africa and the Sahel Region - Davies, Joseph; Kamara, John Kukuba; Kanu, Santigie Dobson (Advances in Social Sciences Research Journal, 2026)
This study interrogates the phenomenon of state failure within the global south, situating its analysis against the governance trajectories of the global north, where institutional integrity, equitable application of the rule of law, and the prioritization of public service over personal gain are more firmly entrenched. Particular emphasis is placed on West Africa and the Sahel region, where recurrent triggers of state fragility, including systemic corruption, protracted civil and domestic conflicts, economic decline, institutional weakness, erosion of sovereignty, and diminished legitimacy in both domestic and international spheres, have undermined developmental progress. Comparative references are drawn from Africa, Latin America, and Asia, highlighting the persistence of predatory governance structures that consolidate resources among narrow elites while perpetuating widespread poverty. By critically examining these dynamics, the paper seeks to elucidate the long-term developmental implications of state failure and to propose contextually grounded strategies for restoration, with special attention to institutional strengthening, conflict resolution, and the re-establishment of public trust in governance across West Africa and the Sahel.